Physical activity and weight gain after smoking cessation in postmenopausal women. Issue 1 (January 2019) - Luo, Juhua; Manson, JoAnn E.; Hendryx, Michael; Shadyab, Aladdin H.; Johnson, Karen C.; Dinh, Paul C.; Going, Scott B.; Chlebowski, Rowan; Stefanick, Marcia L.; Margolis, Karen L.
Abstract: Objective: Weight gain frequently occurs after smoking cessation. The objective of this study was to examine whether weight gain after smoking cessation was attenuated by physical activity (PA) in postmenopausal women. Methods: A total of 4, 717 baseline smokers from the Women's Health Initiative were followed for 3 years. One thousand two hundred eighty-two women quit smoking, and 3, 435 continued smoking. Weight was measured at baseline and at the year 3 visit. PA was assessed at both times by self-report, summarized as metabolic equivalent task-hours per week. Multiple linear regression models were used to assess the association between PA and postcessation weight gain, adjusting for potential confounding factors. Results: Compared with continuing smokers, quitters gained an average of 3.5 kg (SD = 5.6) between the baseline and year 3 visit. Quitters with decreased PA had the highest amount of weight gain (3.88 kg, 95% CI: 3.22-4.54); quitters with increased PA (≥15 metabolic equivalent task-hours /week) had the lowest weight gain (2.55 kg, 95% CI: 1.59-3.52). Increased PA had a stronger beneficial association for postcessation weight gain for women with obesity compared to normal weight women. Quitters who had low PA at baseline and high PA at year 3 and were also enrolled in a dietary modification intervention had nonsignificant weight gain (1.88 kg, 95% CI: −0.21-3.96) compared with continuing smokers. Conclusions: Our data demonstrate that even a modest increase in PA (equivalent to current recommendations) can attenuate weight gain after quitting smoking among postmenopausal women, especially in combination with improved diet. Abstract : Supplemental Digital Content is available in the text